Pengaruh Kualitas Pelayanan dan Lokasi terhadap Kepuasan Konsumen - Ria, Anastasia Mince; Andari, Titiek Tjahja; Yulianingsih, Yulianingsih (Jurnal Ekonomi & Bisnis, 2024)
Consumer satisfaction is an indicator of success that every organization wants to achieve. There are several factors that influence this, including service and location. The purpose of this study is to ascertain the simultaneous and partial effects of service quality and location on customer satisfaction. This study's variables are independent variables: service quality (X1), which is related to tangible evidence; location (X2), which refers to access, visibility, traffic, parking, and environment; and consumer satisfaction (Y), which is related to appropriate expectations, desire to visit, and willingness to authorize. Purposive sampling was used to choose the study's 100 participants, who were customers of the Falsafah Ngopi Ciherang Bogor store. There are two types of research: verification and descriptive. Methods for gathering data via questionnaires. Using the IBM SPSS 26 analysis tool, multiple linear regression was performed for data analysis. According to the study findings, customer satisfaction (Y) was positively correlated with service quality (X1), and location (X2), all of which were rated highly by customers. Both location and service quality positively and significantly affect customer satisfaction simultaneously, and they also positively and significantly affect customer satisfaction to some extent. Because personnel are often not attentive when fulfilling customer demands, location and service quality can positively impact customer satisfaction. This is demonstrated by the research findings on location appearance, which have a strong and significant impact on customer satisfaction.